Nowele jako materiał dydaktyczny rozwijający kompetencje socjokulturowe i socjolingwistyczne .......... 81 - Rumińska, Magdalena (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
NOVELLAS AS A DIDACTIC MATERIAL DEVELOPING SOCIOCULTURAL AND SOCIOLINGUISTIC COMPETENCESThe article outlines issues concerning the development of sociocultural and sociolinguistic competences during the Polish as a foreign language classes with the utilisation of literary texts. In such a context, two chosen aspects were focused on, i.e. the phraseology in its broadest sense and tabooed and marginalised topics in the glottodidactic process. Positivist and Young Poland movement novellas from two original studies were used as didactic material. Using selected works as examples, methods of working with texts were proposed and the examples of exercises, whose goal is to develop the previously mentioned competences were discussed. In addition, the purpose of the article was to show that past literary texts make a valuable source of knowledge on Polish culture and its linguistic creations (e.g. phraseologisms, sayings or so-called catchphrases).